Paranormal belief, cognitive-perceptual factors, and well-being: A network analysis - Dagnall, Neil; Denovan, Andrew; Drinkwater, Kenneth G. (Frontiers in Psychology, 2022)
By assessing interrelationships among variables within a specified theoretical framework, network analysis (NA) provides nuanced insights into how associations between psychological constructs are related to outcome measures. Noting this, the authors used NA to examine connections between Paranormal Belief, cognitive-perceptual factors (Schizotypy, Transliminality, Manic-Depressive Experience), and well-being (Life Satisfaction, Meaning in Life, Somatic Complaints, Perceived Stress, Depressive Symptoms). Data derived from a sample of 3090 participants (mean age = 50.30, standard deviation = 15.20; 46.5% male, 53.1% female) who completed standardised self-report measures capturing the study constructs online. Transliminality, Unusual Experiences (positive schizotypy), and Depressive Experience demonstrated high expected influence centrality. This indicated that these factors were the most strongly connected and influential in the network. Moreover, Transliminality was a connecting variable between Paranormal Belief, positive schizotypy, and psychopathology. Depressive Experience bridged the relationship between Transliminality and well-being. The conceptual implications of these outcomes are discussed with regards to better understanding relationships between Paranormal Belief, cognitive-perceptual factors, and well-being.